Using low dose x-ray speckle visibility spectroscopy to study dynamics of soft matter samples. (29th September 2021) - Möller, Johannes; Reiser, Mario; Hallmann, Jörg; Boesenberg, Ulrike; Zozulya, Alexey; Rahmann, Hendrik; Becker, Anna-Lena; Westermeier, Fabian; Zinn, Thomas; Sprung, Michael; Narayanan, Theyencheri; Gutt, Christian; et al.
Abstract: We demonstrate the successful application of x-ray speckle visibility spectroscopy (XSVS) experiments to study the dynamics of radiation sensitive, biological samples with unprecedented small x-ray doses of 45 Gy and below. Using XSVS, we track the dynamics of casein micelles in native, concentrated, and acidified solution conditions, while substantially reducing the deposited dose as compared to alternative techniques like sequential x-ray photon correlation spectroscopy. The Brownian motion in a skim milk sample yields the hydrodynamic radius of the casein micelles while deviations from Brownian motion with a characteristic q -dependent diffusion coefficient D ( q ) can be observed in more concentrated solution conditions. The low dose applied in our experiments allows the observation of static, frozen speckle patterns from gelled acidic milk. We show that the XSVS technique is especially suitable for tracking dynamics of radiation sensitive samples in combination with the improved coherent properties of new generation x-ray sources, emphasizing the great potential for further investigations of protein dynamics using fourth generation synchrotrons and free electron lasers.